The Influence of Byzantine Law in East Central Europe - Šarkić, Srđan (Lectures on East Central European Legal History, 2023)
The first part of the chapter is dedicated to the sources of Byzantine law, secular and ecclesiastical. The most important secular laws are: 1) the Farmer’s Law from the 7th or 8th century, concerning the peasantry and the villages; 2) Ecloga (726 or 741) issued by Emperor Leo III and his son Constantine V; 3) Legislation of Macedonian dinasty or the so-called ‘Recleansing of the Ancient Laws’, includig Epanagoge, Procheiron, Basilika, and the Novels of Leo VI; 4) Hexabiblos (Six Books), which is a private codification, compiled by Constantine Harmenopoulos, judge of Thessalonica; 5) Peira, a collection of excerpts from the statements of verdicts and special treaties of Eustathios Rhomaios, judge at the imperial court. The most important ecclesiastical laws are: 1) Synopsis canonum, a summary of abridged canons, arranged in alphabetical or chronological order; 2) ‘Systematic collections’, Synagoge, and Syntagma canonum, organized by topic; 3) Nomokanons, compilations of secular laws and canons; and 4) Matheas Blastares’ Syntagma and Constantine Harmenopoulos’ The Epitome of the Holy and Divine Canons. The second part of the text treats the reception of Byzantine law in Slavonic countries: 1) Slavonic Ecloga and the oldest preserved Slavonic legal text Zakon Sudnyj Ljudem (Law for Judging the People or Court Law for the People); 2) the Slavonic Nomokanons or Kormchaia kniga; and 3) the Stefan Dušan’s Codification, consisting of the Serbian translation of Matheas Blastares’ Syntagma, Justinian’s law (short compilation of 33 articles regulating agrarian relations), and Dušan’s Law Code in the narrow sence. Third part of the chapter refers to the reception of Byzantine law in Danubian Principalities (Wallachia and Moldavia) transmitted through the Serbs and the Bulgars and their processed Slavic legalworks, received through Byzantine officials and through the church. The last part of the text is dedicated to the Byzantine public law’s ideas in East Central Europe. The most important and common ideas espoused in the work are: 1) the Roman, Byzantine, and Slavonic concept of law; 2) the idea of Rome and a hierachical world order; 3) the Emperor’s task; 4) concordance or ‘symphonia’ between the church and the state; and 5) the concept of the state.KEYWORDS: Farmer’s Law, Ecloga, Epanagoge, Procheiron, Basilika, Novels of Leo VI, Hexabiblos, ‘Systematic collections’, Nomokanons, Syntagma, Zakon Sudnyj Ljudem, Kormchaia kniga, Stefan Dušan’s codification, Danubian Principalities, concept of law, hierarchical world order, the Emperor’s task, symphonia.